Case studies in food policy for developing countries. - Pinstrup-Andersen, Per; Cheng, Fuzhi (Cornell University Press, 2009)
Volume II of the Case Studies addresses the issues of domestic policies for markets, production, and the environment.
Keywords: Nutrition policy -- Developing countries -- Case studies.; Food supply -- Developing countries -- Case studies.; Agriculture and state -- Developing countries -- Case studies.; Agriculture -- Economic aspects -- Developing countries -- Case studies.; BUSINESS & ECONOMICS -- Industries -- General.; Agriculture and state; Agriculture -- Economic aspects; Food supply; Nutrition policy; Developing countries; Case studies